2006
DOI: 10.1021/es0515957
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-Borne Quinones and Reactive Oxygen Species Generation by Particulate Matter Extracts

Abstract: The mass loadings of quinones and their ability to generate reactive oxygen species (ROS) were investigated in total suspended particulate samples collected in Fresno, CA, over a 12-month period. Particles were collected on Teflon filters and were analyzed for the presence of 12 quinones containing one to four aromatic rings by gas chromatography with mass spectrometry. Measured levels are generally greater than mass loadings reported at other locations. The mass loadings were highest during winter months and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
176
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(194 citation statements)
references
References 36 publications
6
176
1
7
Order By: Relevance
“…The atmospheric concentrations found for 9,10-AQ are in the same order of magnitude than those already reported in an earlier studies in Guadalajara [18], while 1,4-NQ concentrations are almost three times higher than those found in Mexico City [19]. Overall, the majority of quinones have the same order of magnitude as those in Fresno, CA, USA, except for 5,12-NQ [20]. They are also similar to those found in Birmingham, UK, except for 9,10-PQ and 1,4-NQ [21,22], but concentrations of quinones in this work were higher than those reported in Santiago and Temuco, Chile [23], and in an Eastern coastal site in the UK [17].…”
Section: Environmental Levelssupporting
confidence: 77%
“…The atmospheric concentrations found for 9,10-AQ are in the same order of magnitude than those already reported in an earlier studies in Guadalajara [18], while 1,4-NQ concentrations are almost three times higher than those found in Mexico City [19]. Overall, the majority of quinones have the same order of magnitude as those in Fresno, CA, USA, except for 5,12-NQ [20]. They are also similar to those found in Birmingham, UK, except for 9,10-PQ and 1,4-NQ [21,22], but concentrations of quinones in this work were higher than those reported in Santiago and Temuco, Chile [23], and in an Eastern coastal site in the UK [17].…”
Section: Environmental Levelssupporting
confidence: 77%
“…Gas-phase quinones may include the highly volatile and reactive 1,2-and 1,4-naphthoquinones (1,2-NQ and 1,4-NQ), while higher molecular weight quinones such as 9,10-phenenthraquinone (PQ) and 9,10-anthraquinone (AQ) are expected to be found mostly in the particle-phase. However previously reported measurements have referred only to quinones associated with PM (Albinet et al 2007;Allen et al 1997;Chung et al 2006;Sienra 2006), and to our knowledge no information regarding ambient gas-phase concentrations is available in the open literature.…”
Section: Introductionmentioning
confidence: 99%
“…Quinones have been shown to be present in ambient particles Chung et al, 2006;Valavanidis et al, 2006;Tsapakis and Stephanou, 2007;Eiguren-Fernandez et al, 2008a;Ahmed et al, 2009) and contribute to particle-bound stable radical species, as measured by electron paramagnetic resonance Pan et al, 2004;Valavanidis et al, 2006). The source of these species may be primary or secondary.…”
Section: Introductionmentioning
confidence: 99%
“…In one such study researchers found that hydrogen peroxide generation from the DTT assay performed on particles from Fresno, California, could be accounted for by measuring the aerosol mass loadings of 9,10-phenanthrenequinone, 1,2-naphthoquinone, and 1,4-naphthoquinone (Chung et al, 2006). In another study, by assigning the DTT loss rate to individual particulate species again from the Fresno area, Charrier and Anastasio were able to predict DTT decay as arising 80 % from transition metal species and 20 % from quinone species (Charrier and Anastasio, 2012).…”
Section: Introductionmentioning
confidence: 99%